Nutrient Film Technique (NFT) Hydroponic Monitoring System - Helmy Helmy; Arif Nursyahid; Thomas Agung Setyawan; Abu Hasan (Politeknik Negeri Semarang, 2016)
Plant cultivation using hydroponic is very popular today. Nutrient Film Technique (NFT) hydroponic system is commonly used by people. It can be applied indoor or outdoor. Plants in this systemneed nutrient solution to grow well. pH, TDS and temperature of the nutrient solution must be check to ensure plant gets sufficient nutrients. This research aims todevelop monitoring system of NFT hydroponic. Farmer will be able to monitor pH, TDS and temperature online. It will ease farmer to decide which plant is suitable to be cultivated and time to boost growth.Delay of the system will be measured to know system performance. Result shows that pH is directly proportional with TDS. Temperature value has no correlation with pH and TDS. System has highest delay during daylight and afternoon but it will decline in the night and morning. Average of delay in the morning is 11 s, 28.5 s in daylight, 32 s in the afternoon and 17.5 s in the night.